(untitled) (International Journal of Medical and Surgical Sciences, 2016)
Flow cytometry is a useful technology in the sexed sperm, which measures and analyzes simultaneously, multiple physical characteristics of the cell, as they flow in a stream flow, through a light beam. The measured properties are the size of a particle, relative internal granularity, relative complexity and relative fluorescence intensity. Currently, hundreds of calves have been gestated through artificial insemination with sexed sperm in animal production. Since 1992, flow cytometry has been used, a technique that allows spermatozoa X and Y differentiation by DNA content. There is no other practical technique for sperm sexing to keep sperm functionality. The objectives of this review are to explain: (1) why the sperm containing the X or Y chromosome are phenotypically similar, but differ among themselves, (2) the principles and procedures used for sexing sperm by flow cytometry and sorting ( 3) accuracy, speed and efficiency of current procedure sperm sexing, (4) sperm damage occurred during sperm sexing and consequently the effects on fertility.